Did the Sarbanes-Oxley Act of 2002 make Firms less Opaque? Evidence from Analyst Earnings Forecasts - Stefan Arping; Zacharias Sautner (Tinbergen Institute, 2010)
We study whether the Sarbanes-Oxley Act (SOX) of 2002 made firms less opaque. For identification, we use a difference-in-differences estimation approach and compare EU firms that are cross-listed in the US—and therefore subject to SOX—with comparable EU firms that are not cross-listed. We derive proxies for corporate opaqueness from analyst earnings forecasts. Our findings suggest that, relative to the control group, cross-listed firms became significantly less opaque after the implementation of SOX. We provide evidence that this effect was particularly pronounced for firms operating in informationally sensitive industries. We complement our analysis with a textual analysis of corporate annual reports in order to shed light on how SOX may have affected firms' reporting behavior.
Keywords: G1; G3; 330; Sarbanes-Oxley Act; Analyst Forecasts; Corporate Governance; Disclosure Regulation; Internes Kontrollsystem; Corporate Governance; Unternehmenspublizität; Vergleich; EU-Staaten; USA